Measurements of Kaon Femtoscopy in Au+Au Collisions at √sNN = 3.0 - 4.5 GeV by the STAR Experiment - Fan Bijun (EPJ Web of Conferences)
In these proceedings, we present the measurements of charged K+ − K+ and neutral KS0, - KS0 correlation functions from Au+Au fixed-target collisions at √sNN = 3.0, 3.2, 3.5, 3.9 and 4.5 GeV at STAR. This is the first such systematic measurement of correlation functions involving strangeness in the high baryon density region. The source size values do not exhibit a clear energy dependence, and the transverse mass dependence of source size for kaons does not align with the trend observed for pions. Parameters extracted from UrQMD transport model calculations qualitatively capture the measured values.